2013
DOI: 10.1242/jeb.087858
|View full text |Cite
|
Sign up to set email alerts
|

Stress and death of cnidarian host cells play a role in cnidarian bleaching

Abstract: SUMMARYCoral bleaching occurs when there is a breakdown of the symbiosis between cnidarian hosts and resident Symbiodinium spp. Multiple mechanisms for the bleaching process have been identified, including apoptosis and autophagy, and most previous work has focused on the Symbiodinium cell as the initiator of the bleaching cascade. In this work we show that it is possible for host cells to initiate apoptosis that can contribute to death of the Symbiodinium cell. First we found that colchicine, which results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 38 publications
(46 reference statements)
5
72
0
Order By: Relevance
“…Further work is needed to fill in these gaps in our knowledge. While we cannot entirely discount symbiont-derived ROS as a stimulus for the host responses observed here, our data support a growing body of work suggesting that host-level mechanisms play an important role in determining the bleaching responses of corals (Nii and Muscatine 1997;Fitt et al 2009;Palmer et al 2010;Dunn et al 2012;Paxton et al 2013;Tolleter et al 2013). …”
Section: Cellular Events In the Coral Hostsupporting
confidence: 71%
See 1 more Smart Citation
“…Further work is needed to fill in these gaps in our knowledge. While we cannot entirely discount symbiont-derived ROS as a stimulus for the host responses observed here, our data support a growing body of work suggesting that host-level mechanisms play an important role in determining the bleaching responses of corals (Nii and Muscatine 1997;Fitt et al 2009;Palmer et al 2010;Dunn et al 2012;Paxton et al 2013;Tolleter et al 2013). …”
Section: Cellular Events In the Coral Hostsupporting
confidence: 71%
“…Overproduction of reactive oxygen species (ROS), the onset of oxidative stress, and subsequent cellular damage were proposed as the proximate causes of this symbiotic collapse (Downs et al 2002). Temperature-and light-induced ROS generation have been experimentally confirmed in Symbiodinium (Lesser 1996;Lesser 2006 for review;Suggett et al 2008;Saragosti et al 2010), but damage to host tissue in the absence of symbiont dysfunction (Gates et al 1992;Nii and Muscatine 1997;Dunn et al 2004Dunn et al , 2012Paxton et al 2013) and the release of photosynthetically competent and viable symbionts from bleaching corals (Ralph et al 2001;Hill and Ralph 2007) have also been reported. Clearly, not all thermal bleaching in corals is symbiontdriven (Baird et al 2008;Tolleter et al 2013).…”
Section: Communicated By Biology Editor Dr Anastazia Banaszakmentioning
confidence: 99%
“…The studies suggested that host cell death can contribute to subsequent symbiont cell mortality, a process that appears similar to a host innate immune response. The results indicated that no single pathway is responsible for symbiont release during bleaching, allowing to formulate a model for cellular processes involved in the control of cnidarian bleaching where apoptosis and autophagy act together in a see-saw mechanism such that if one is inhibited the other is induced (Dunn et al 2007;Weis 2008;Paxton et al 2013).…”
Section: Autophagy Induced By Environmental Stress On Aquatic Invertementioning
confidence: 99%
“…Moreover, while some intracellular sites and effects of thermal damage in the host and symbiont have been identified, there is no consensus about the causal chain of events and the supposed 'weak link' in the symbiosis. Indeed, bleaching can be manifested as host-cell detachment and/or release of potentially photosynthetically competent symbionts (Gates et al, 1992;Ralph et al, 2001), as well as breakdown of photosynthetic dark and light reactions (Jones et al, 1998;Warner et al, 1999), and apoptosis and necrosis in both partners (Dunn et al, 2004;Tchernov et al, 2011;Hawkins et al, 2013;Paxton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%